RADIKAL FORTOLKNING: Humanistisk teori ved årtusindskiftet - Hastrup, Kirsten (Tidsskriftet Antropologi, 1999)
The renaissance view of humans as ffee and responsible agents is the starting point for this article that seeks to delineate the task of the humanities today, at an age which has had to accept the fail of Objectivism. The time is marked by a switch from seeing the task of science in general as one of clarifying what is already there, in nature, to seeing it as a kind of radical interpretation that adds its own layer of understanding, and thereby of reality, to the object. The conclusion is that the object of study for the human Sciences cannot and should not be seen in naturalistic terms; instead we have to work with fluid objects and ontologies that seriously question the disciplinary boundaries established in the nineteenth century.